Inappropriate Antibiotic Utilization: Outpatient Prescription Review of a Regional Secondary Hospital in Kedah, Malaysia - Tan, Guo-Hong; Low, Qiau-Wei; Lim, Huey-Chyi; Seah, Hui-Koon; Chan, Huan-Keat (Journal of Pharmacy Practice and Community Medicine)
Background: The National Antibiotic Guideline (NAG) was introduced in Malaysia in 2014, and has since become the guidance for antibiotic prescribing, especially in public health centers where infectious disease specialists, local antibiotic guidelines and clinical microbiology services are not readily available. This study was designed to assess the patterns of antibiotic use for a range of diseases in the outpatient department of a regional secondary hospital, and the level of adherence to the NAG among the prescribers. Methods: A cross-sectional study was undertaken at the Sik Hospital, Kedah. All oral antibiotic-containing prescriptions of adult outpatients dispensed during 1st May and 31st July 2016 were reviewed. The information on each prescription, including age, diagnosis, and the type and dosage of the antibiotic prescribed, was recorded on an electronic data collection sheet. Results: Of 8,312 prescriptions screened, 662 (8%) contained at least one oral antibiotic. Inappropriate selection of antibiotics was found in approximately 40% of the prescriptions with clear diagnoses, the majority (79.2%) of which involved the use of erythromycin ethylsuccinate for upper respiratory tract infections (URTIs). Besides, by comparing the defined daily dose (DDD) of each antibiotic with the maximum DDD as recommended in the NAG, inappropriate dosage and treatment duration were found in five antibiotics, particularly those prescribed for the treatment of URTIs and urinary tract infections. Conclusion: As antimicrobial resistance has become a major concern worldwide, the findings warrant immediate attention and a well-planned approach to improve the antibiotic prescribing practice among the secondary hospitals in Malaysia.
Keywords: Anti-Bacterial Agents; Drug Resistance; Inappropriate Prescribing; Malaysia; Outpatients